The Effect of Green Marketing and Brand Image on Purchasing Decisions Through XYZ Online Application - Ferdhy Febryan; Mochammad Mukti Ali (Dinasti Publisher, 2024)
This study was conducted to reveal the impact or effect of Green Marketing and Brand Image in Purchase Decission. The object of this study is online e-commecre platform from one the major supermarket in Indonesia. This supermarket starting to implement the green marketing strategy although they do not claim that they do green marketing, but what they do is closing to green marketing strategy. This major supermarket has a good brand image for offline store but not online. The method used in this research is quantitative method with 300 sample and using regresion analysis to uncover the effect of Green Marketing and Brand Image in Purchase Decision impact to Purchase Decission. The result of this study indicates that both green marketing and brand image has positive impact on puchase decission. The impact is partial also simulataneously. This result giving an insight for that major supermarket to reconsider their strategy especialy on Green Marketing and Brand Image in online platform.